PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2012-2014) - Wijaya, Mateus; ', Yusralaini; ', Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to find out about the effect of the audit comittee, independent directors, institusional ownership, managerial ownership, and Corporate Social Responsibility on company’s value. The method used in this research is purposie sampling method premises comparative analysis of samples of specified research during 2012 to 2014. The sample was state-owned companies in all fields. Hypothesis testing is to test the hypothesis of partial analysis (t test). Tools used statistical test is progam Statistical Product and Service Solution (SPSS) ver. 20. 0 for Windows and Microsoft Excel 2010, while the data used in the form of data each company’s annual report are sampled, the Indonesia Stock Exchange 2012-2014. The results showed that the audit comittee, independent director, institusional ownership, managerial ownership, and corporates social responsibility do not affect the value of the company but have a positive relationship. This has become one of the proofs that the implementation of good corporate governance and corporate social responsibility in company SOEs in Indonesia has not been implemented properly, this can be seen from the disclosure of good corporate governance and corporate social responsibility is still relatively low.Keywords : Good Corporate Governance, Corporate Social Responsibility, Company’s Value.